2008
DOI: 10.1182/blood-2006-07-037572
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase B (c-akt) regulates hematopoietic lineage choice decisions during myelopoiesis

Abstract: Hematopoiesis is a highly regulated process resulting in the formation of all blood lineages. Aberrant regulation of phosphatidylinositol-3-kinase (PI3K) signaling has been observed in hematopoietic malignancies, suggesting that regulated PI3K signaling is critical for regulation of blood cell production. An ex vivo differentiation system was used to investigate the role of PI3K and its downstream effector, protein kinase B (PKB/c-akt) in myelopoiesis. PI3K activity was essential for hematopoietic progenitor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 44 publications
2
92
0
Order By: Relevance
“…As a result, the phosphorylation of cell cycle inhibitory protein p21 cip1 , a target of Akt, is enhanced, leading to diminished cell cycle inhibitory effect of p21 cip1 . 13 Collectively, these results established InsP3KB as a negative regulator of myeloid differentiation and neutrophil production.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 80%
See 1 more Smart Citation
“…As a result, the phosphorylation of cell cycle inhibitory protein p21 cip1 , a target of Akt, is enhanced, leading to diminished cell cycle inhibitory effect of p21 cip1 . 13 Collectively, these results established InsP3KB as a negative regulator of myeloid differentiation and neutrophil production.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 80%
“…The accelerated proliferation of granulocyte monocyte progenitors may be a result of enhanced PtdIns(3,4,5)P3/Akt signaling, which has been recently implicated in myelopoiesis. 13 This signaling pathway was previously thought to be dependent solely upon concentrations of PtdIns (3,4,5) P3 in the plasma membrane. 14,15 Recently, we demonstrated that two inositol phosphates, InsP7 and Ins(1,3,4,5)P4, compete for Akt-PH domain binding with PtdIns(3,4,5)P3 both in vitro and in vivo, providing another level of regulation for Akt membrane translocation and activation.…”
Section: Ins(1345)p4 and Insp3kb Regulate Innate Immunity Via Modumentioning
confidence: 99%
“…Human CD34 + hematopoietic progenitor cells, isolated from umbilical cord blood, were cultured in the presence of either G-CSF or IL-3 and IL-5 to induce neutrophil and eosinophil differentiation, respectively. Cells were cultured in either the absence or presence of rapamycin, a specific pharmacological inhibitor of mTOR, and differences in expansion were determined both by analysis of the number trypan bluenegative cells as well as by performing 3 H-thymidine incorporation assays. Rapamycin reduced expansion during neutrophil differentiation ( Figure 1A, 1B).…”
Section: Inhibition Of Rapamycin-sensitive Mtor Signaling Decreases Cmentioning
confidence: 99%
“…2 It has, for example, been demonstrated that PI3K plays an essential role in regulation of hematopoietic progenitor survival and expansion during myelopoiesis. 3 Furthermore, impaired regulation of PI3K and its downstream effector protein kinase B (PKB/c-akt) has been implicated in carcinogenesis. In particular, activation of the PI3K/PKB signaling module is observed in a variety of hematopoietic malignancies, including acute leukemias and high-risk myelodysplastic syndromes.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has very recently been shown that the MEK/ERK pathway is involved in myeloid lineage commitment (3). Also, PKB (c-Akt) was shown to be involved in lineage decision during myelopoiesis (4). In addition, FLT3-activating mutations were proved to inhibit C/EBP␣ activity through ERK1/2-mediated phosphorylation (3,5).…”
mentioning
confidence: 99%